KERJA LAYAK DORONG PERKEMBANGAN INDUSTRI PARIWISATA DI KEDONGANAN DAN JIMBARAN BALI - Bambang Suharto; Janianton Damanik; Muhammad Baiquni; Chafied Fandeli (Jurnal Kawistara, 2016)
The decent work has become an obligatory in the tourism industry. This work has been able to ensureproperly the needs of workers, families, and their social life, productive and prosperous. This researchfocuses on the study of generated effects of the decent work. Theoretical framework of the ILO decentwork (2009a) was used as the guidance framework to answer and find the actual implementation inthe tourism industry.The study used quantitative method as the basis of analysis towards the datawhich were collected through questionnaires. The result indicated that the effect of the decent work onthe development of tourism industry reached 68%. This result was in good enough category scale. Inthe scope of this value, the decent work showed the empirical reality gave further effect towards thetourism forms based on prosperity and sustainability